Najdawniejsze zapiski z księgi miejskiej Pleszewa (1428-1444). Wyd. Tomasz Jurek, 2011 - Kozak, Adam (Czasopismo Prawno-Historyczne, 2018)
Najdawniejsze zapiski z księgi miejskiej Pleszewa (1428-1444). Wyd. Tomasz Jurek, 2011